REVIVAL OF THE LA TÈNE TRADITION IN THE MIDDLE BALKANS IN THE 3RD CENTURY AD - Černač Ratković, Snežana (Rei Cretariae Romanae Fautorum Acta, 2024)
Modern Ćuprija (Horreum Margi), lies at the right bank of the river Morava (Margum), in the central part of Serbia. Thanks to its favourable position, at the crossroads of several land- and fluvial roads, it developed rapidly during the Roman Imperial period. This conclusion can be drawn because of its name Horreum. This town is considered to be one of the most important food distributors for the military stationed along the right Danube bank in the Iron Gate district.